Villagers’ perspective of contributing factors to illegal logging and land encroachment in Ulu Sat Permanent Reserve Forest, Kelantan, Malaysia - Mohamad Amran, Nur Afifah (2019)
Ulu Sat Permanent Reserve Forest (PRF) comprises of three recreation areas, namely Jeram Linang, Bukit Baka and Lata Tujuh located within the Ulu Sat district of Machang, Kelantan. Ulu Sat PRF is comprises of 14,432 hectares of forest reserves area. There are 12 sub-districts of Ulu Sat, namely Baka, Bakat, Banggol Judah, Belukar, Bukit Tiu, Cherang Hangus, Kemuning, Kepang, Kepas, Kweng Hitam, Pangkal Durian and Sungai Hala that accommodate with total population of 29.233 people comprising Malay (92.20%), Chinese (7.63%), Indian (0.10%) and others (0.07%). Illegal logging and land encroachment are increasingly prevalent in Ulu Sat PRF as intruders gain access via the recreation areas. The first objective of this study was to identify villagers’ consciousness about the types of forest offences commonly committed by intruders. The second objective was to classify the factors of illegal logging and land encroachment. The third objective was to assess villagers’ perceptions of illegal logging and land encroachment based on age. The study was conducted through interviews using questionnaires in cooperation with the village headman by selecting 360 respondents from 69 villages in the 12 sub-districts. By using random sampling, respondents were aware of the forest offences that occurred in the study area. Data from the study were analysed using IBM SPSS (Statistical Package for Social Science) version 24.0. The villagers were aware that most common offence being timber extraction without a licence (67.5%). The least common infringement was poison fishing, disposal of toxic substances or fish bombs in rivers or lakes (30.8%). Principal Component Analysis (PCA) revealed that enforcement (20%), economic (15.6%), socioeconomic (15%) and human-attitude (11%) were the main factors for illegal logging. While enforcement (22%), locality (21%) and knowledge (11%) were the main factors for land encroachment. As for the villagers’ perception based on age, it was influenced by high cost of living (0.001), jobless/fixed income (0.003), lack of awareness about illegal logging activities (0.046) and lack of knowledge about forest management (0.004). For land encroachment, the three significant factors are lack of knowledge about the law (0.042), land sales syndication (0.006) and weak law enforcement (0.025). Therefore, this study is able to find out clearly the factors that cause the occurrence of forest offenses in the study area from the perspective of the villagers. Subsequently, the outcome of this study could be channelled to the State of Kelantan Forestry Department to assist them in obtaining information to address the difficult issues of this uncontrolled forest offense.